Impact of sensory interventions on the quality of life of long-term care residents: a scoping review. Issue 3 (24th March 2021) - Backman, Chantal; Demery-Varin, Melissa; Cho-Young, Danielle; Crick, Michelle; Squires, Janet
Abstract : Introduction and purpose: Residents in long-term care exhibit diminishing senses (hearing, sight, taste, smell or touch). The purpose of this study was to examine the available literature on the impact of sensory interventions on the quality of life of residents living in long-term care settings. Methods: We conducted a mixed-methods scoping review using Arksey and O'Malley's framework. Seven databases (Medline (Ovid), PubMed (non-Medline-Ovid), CINAHL (EBSCO), Embase (Ovid), Ageline, PsycINFO (Ovid), Cochrane Central Register of Controlled Trials until 1 December 2020) were searched. Two reviewers independently screened the studies for sensory interventions using a two-step process. Eligible studies underwent data extraction and results were synthesised descriptively. Results: We screened 5551 titles and abstracts. A total of 52 articles met our inclusion criteria. Some interventions involved only one sense: hearing (n=3), sight (n=12), smell (n=4) and touch (n=15). Other interventions involved multiple senses (n=18). We grouped the interventions into 16 categories (music programmes, environmental white noise, bright light interventions, visual stimulations, olfactory stimulations, massages, therapeutic touch, tactile stimulations, physical activity plus night-time programmes, pet therapies, various stimuli interventions, Snoezelen rooms, motor and multisensory based strategies, Namaste care, environmental modifications and expressive touch activities). Conclusion: This preliminary review summarised some of the available sensory interventions that will help inform a series of future systematic reviews on each of the specific interventions. The evidence-based knowledge for sensory interventions will also inform a future audit programme for assessing the presence of sensory interventions in long-term care.